Pharmacokinetics and Biopharmaceutics - G Victor Rajamanickam (New Academic Publishers, 2009)
In addition to introduction, the book include chapters on Pharmacokinetics of Oral Administration, Application of Pharmacokinetics in the Elderly, Non Carcinogenic Risks, Drugs Abuse, Dynamic Systems Theory, Chronic Effects, Clinical Research, Priorities for Risk Assessment, which deal the subject in simple way. The book is useful for students and teachers.